EKSPLOITASI ORANG TUA TERHADAP ANAK (Studi: Pekerja Anak di Kelurahan Seberang Palinggam Kecamatan Padang Selatan, Kota Padang) - AYU, NELSI PUTRI (Pendidikan Sosiologi, 2014)
Every child has a right to be protected , in Article 2 of Law No. 4 of1979 states : (1) Children are entitled to welfare, treatment, care and guidancebased on affection in his family to grow and develop naturally. (2) The child isalso entitled to the services to develop abilities and social life. (3) The child isentitled to maintenance and protection, both during in utero and after birth. (4)Children are entitled to protection of the environment, which may jeopardize orhamper the normal growth and development, as well as protection from violenceand discrimination, in order to achieve quality of Indonesian children, morals, andwelfare. Furthermore, Article 20 requires that the state, government, communities,families and parents to take responsibility for child protection. The fact that thecase is still a lot of parents who allow children to work in a dangerous place forchildren and violate the rights of children, such as the existence of child laborunder 15 years of age who come from the village of Padang District PalinggamAcross South. This study used a qualitative approach and descriptive. The datacollection techniques in this study in the form of in-depth interviews, observationand study document. Unit data analysts in this study is a family consisting ofparents and children. From the research it can be concluded that the parents hadbeen in the exploitation of children under the age of 15 years that is in violation ofthe law on the protection of the rights of the child, such as: children forced towork in dangerous conditions for development, health and safety of children, thetime spent with the child work that is more than three hours a day, and the wagesearned working children are given to parents. Then with the employment ofchildren will have a negative impact on children : First, the impact on growthboth in terms of physical, psychological and social. Second, the impact onchildrens education .